Re-envisioning English-Medium Instruction in K-12 Schools Policy, Research and Practice - Gu, Michelle Mingyue; Liu, Yiqi; Huang, Corey Fanglei (Springer Nature Switzerland : Imprint: Springer, 2025)
XIV, 192 p. 63 illus., 28 illus. in color.